Analisis waktu tunggu rata-rata operator angkutan ojek di Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The existence of ojek is an evident that the formal public transport has limitation in its operation and services. The operation and service of ojek is more attractive compared to the formal public transport in terms of that they could serve door to door and at flexible time operation, albeit with more expensive tariff The intension of the research is to investigate the characterisitics of ojek operation with focussing on operator's waiting time. Based on this study a further operation management could be carried out to increase the operation performance of ojek. A survey to the operators Yogyakarta and its surounding. average waiting time of ojek is influenced by the queueing system at stations. Those who don't have queueing system at stations experience waiting time of 1.49 hours and those who have it experience waiting time of 1.93 hours.